THE EFFECT OF ADVERTISING MEDIA ON PURCHASE INTENTION ACER NOTEBOOK IN STUDENTS - Primandini, Apsilia (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstractManufacturers will try to market their business in such a way so that the product can be run as desired, by building effective communication with consumers, one of them through advertising. An advertising that could persuade the consumers successfully can not be separated from the role due to a media message through the right media advertising persuasion will be up to both the consumer. Each medium has a different effect on purchase intention and consumer behavior. The purpose of this study was to determine differences in the effect of media advertising on intention to buy Acer laptops to students. Researchers used the counterbalance experimental design those involving 36 subjects derived from industrial engineering students. Purchase intentions research subjects measured using a scale that is based on intention to purchase aspects of intention by Ajzen (2005) consists of 30 items. Based on the analysis of the paired sample t-test obtained p = 0, 403, p > 0.05 so it can be concluded that there is no difference in the effect of advertising media on intention to buy Acer notebook to students.Â Keyword: counterbalance design, purchase intention, advertising media